Securing IoT Data Using Steganography: A Practical Implementation Approach - Fatiha Djebbar (MDPI AG, 2021)
Adding network connectivity to any “thing” can certainly provide great value, but it also brings along potential cybersecurity risks. To fully benefit from the Internet of Things “IoT” system’s capabilities, the validity and accuracy of transmitted data should be ensured. Due to the constrained environment of IoT devices, practical security implementation presents a great challenge. In this paper, we present a noise-resilient, low-overhead, lightweight steganography solution adequate for use in the IoT environment. The accuracy of hidden data is tested against corruption using multiple modulations and coding schemes (<semantics>MCSs</semantics>). Additive white Gaussian noise (<semantics>AWGN</semantics>) is added to the modulated data to simulate the noisy channel as well as several wireless technologies such as cellular, WiFi, and vehicular communications that are used between communicating IoT devices. The presented scheme is capable of hiding a high payload in audio signals (e.g., speech and music) with a low bit error rate (<semantics>BER</semantics>), high undetectability, low complexity, and low perceptibility. The proposed algorithm is evaluated using well-established performance evaluation techniques and has been demonstrated to be a practical candidate for the mass deployment of IoT devices.